Feasibility of Robotic-Assisted Laparoscopic Nephroureterectomy in Left Ventricular Assist Device Patient. (10th October 2012) - Khemees, Tariq A.; Shabsigh, Ahmad
Abstract : Left ventricular assist devices (LVADs) have revolutionized management options for patients with advanced heart failure. It is not uncommon for patients treated with these devices to present with noncardiac surgical conditions including urologic problems. Maintaining perioperative hemodynamic and hematologic stability is a special challenge. The minimally invasive surgery provides well-documented advantages over the open approach including a less operative blood loss and faster convalescence. In carefully selected patients, robotic-assisted surgery can be utilized in the management of patients with complex urologic diseases in a dire need for these benefits. We present the first case of robotic-assisted laparoscopic nephroureterectomy (RANU) with retroperitoneal lymph node dissection for upper tract transitional cell carcinoma (TCC) in a patient treated with LVAD.